A rare example of a double metamagnetic transition leading to 2D and 3D long-range order in the two-dimensional pyrazine- and azido-bridged cobalt(ii) compound [Co(pyz)(N3)2]. Issue 14 (23rd March 2022) - Setifi, Zouaoui; Setifi, Fatima; Benmansour, Samia; Liu, Xiangyu; Mague, Joel T.; Gómez-García, Carlos J.; Konieczny, Piotr; Reedijk, Jan
Abstract : The two-dimensional Co(ii ) compound [Co(N3 )2 (pyz)] has double azido(κN 1, N 1 ) and pyrazine bridges and shows a double metamagnetic transition to 2D and 3D ferromagnetic phases at 8.0 and 4.5 K with critical fields of 200 and 400 mT, respectively. Abstract : The synthesis, characterization, crystal structure and detailed magnetic properties of a pyrazine (pyz) and azido (N3 ) bridged cobalt(ii ) compound of formula [Co(N3 )2 (pyz)] (1 ) are reported. Compound 1 shows a layered structure formed by Co(ii ) chains with double μ-N3 (κN 1, N 1 ) bridges that are further connected by μ-(pyrazine-κN 1, N 4 ) bridges. The layers present weak van der Waals interactions between azido terminal groups. The magnetic properties show the presence of a metamagnetic behaviour in 1 with two critical fields of 200 and 400 mT at low temperatures. AC magnetic measurements show the presence of a long-range 2D ferromagnetic order at T c ≈ 8.0–7.0 K for dc fields above 200 mT and a long-range 3D ferromagnetic order at T c ≈ 4.5 K for dc fields above 400 mT.